Psychoeducation Stop Bullying For Better Future Among Students Of SMK 2 Penajam Paser Utara - Sukeksi Dyah Intanningrum; Hesti Perwatih; Iswinarti Iswinarti (Eduvest - Journal of Universal Studies, 2024)
The objective of the psychoeducational program "Stop Bullying for Better Future" is to provide understanding about bullying and its impacts on the future to the students of SMKN 2 Penajam Paser Utara, North Kalimantan. This is done because based on the analysis of psychoeducational needs and the academic achievements of these students have decreased due to the prevalent bullying behavior among peers. This activity involves all students from grades X, XI, XII, and as the target/pilot project, the activity focuses on students from the XI Computer Engineering class who are mentored by one of the speakers. The activity is conducted through a Zoom link and sociodrama games performed by the students. The T-test analysis results from the pre-test and post-test conducted showed a significance value of 0.045, where this value is smaller than 0.05, indicating a significant influence of psychoeducation on the understanding of the students of SMKN 2 Penajam Paser Utara. However, the behavior change cannot be determined yet because the psychoeducation conducted targets cognitive and affective aspects rather than behavior change. In the role-playing game, the students showed varied impressions according to the roles they played, as victims of bullying, perpetrators, and bystanders.